2017
DOI: 10.1016/j.foodchem.2017.03.115
|View full text |Cite
|
Sign up to set email alerts
|

Protein interactions during flour mixing using wheat flour with altered starch

Abstract: Wheat grain proteins responses to mixing and thermal treatment were investigated using Mixolab-dough analysis systems with flour from two cultivars, Ventura-26 (normal amylose content) and Ventura-19 (reduced amylose content). Size exclusion high performance liquid chromatography (SE-HPLC) and two-dimensional gel electrophoresis (2-DGE) analysis revealed that, stress associated and metabolic proteins largely interacted with dough matrix of Ventura-26 after 26min (56°C); gliadins, avenin-like b proteins, LMW-GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
(29 reference statements)
0
15
0
1
Order By: Relevance
“…According to Osborne, wheat proteins can be divided into three major types, depending on their functionality: simple, conjugated, and derived. In addition to this classification, single proteins can still be subdivided according to their solubility as previously mentioned …”
Section: Methods Of Starch Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Osborne, wheat proteins can be divided into three major types, depending on their functionality: simple, conjugated, and derived. In addition to this classification, single proteins can still be subdivided according to their solubility as previously mentioned …”
Section: Methods Of Starch Extractionmentioning
confidence: 99%
“…Protein solubility reflects the balance between protein–solvent (hydrophilic) and protein–protein (hydrophobic) interactions. The protein–starch interactions occur due to the electrostatic attraction of opposite charges—i.e., between the negatively charged protein molecules and the positively charged starch granules …”
Section: Introductionmentioning
confidence: 99%
“…For each protein band sample, 125 nanograms of trypsin were added for digestion. The protein spots identification by MS/MS were as previously described [53].…”
Section: Protein Identification By Ms/msmentioning
confidence: 99%
“…A recent proteomic study indicated that drought stress affects the expression of wheat storage proteins, such as gliadins, glutenins and ALPs as early as 3 days after pollination (DAP), moreover, the misregulated expression is associated with cytoskeleton organization and grain quality proteins in developing seeds [52]. Using Mixolab-dough analysis systems, Wang et al [53] reported that the starch surface proteins (gliadins, b-type ALPs, LMW-GSs, and partial globulins) in common wheat and waxy wheat displayed different performance to mixing and thermal treatment. Recently, many storage proteins, including HMW-GS, gliadins, globulins, ALPs, triticins, and ωsecalins have been identified in wheat endosperm and embryo, which displayed differential accumulation at the protein level between two wheat species that are distinct in grain weight and dough quality, suggesting that ALPs are responsible partly for the quality differences [54].…”
Section: Introductionmentioning
confidence: 99%
“…Baking quality of wheat products such as cookies and bread are depending on the starch molecular structure and its properties [24]. Lipids, protein and starch are main component of wheat flour [25]. Despite of being world's leading food component, high consumption of wheat-based product can result in a negative health impact such as obesity and type 2 diabetes [26].…”
Section: Starchmentioning
confidence: 99%